AN INVESTIGATION OF TEACHERS' SELF-SABOTAGE LEVELS - Cömert, Melike; Tekin, Tuğçe (International Online Journal of Education and Teaching, 2024)
This study aims to determine the level of self-sabotage of teachers working in educational institutions and whether this level is affected by demographic variables. For this purpose, the Survey Model, one of the quantitative research methods, was used. The population of the study consists of teachers working in Battalgazi and Yeşilyurt districts of Malatya province in the 2020-2021 academic year. The research was conducted with 151 teachers selected from the population by Stratified Sampling method. The Self-Sabotage Scale developed by Jones and Rhodewalt (1982) and adapted into Turkish by Akın, Abacı, and Akın (2011) and the Personal Information Form prepared by the researcher were used to determine the self-sabotage levels of teachers. Since the data were normally distributed, parametric tests (Independent Groups T-Test and One Way ANOVA) were preferred. In cases where the number of people in the sub-sample groups fell below 30, non-parametric tests (Mann-Whitney U Test and Kruskal-Wallis H Test) were used. As a result of the study, it was determined that teachers showed a partially low level of self-sabotage tendency. A significant difference was found between self-sabotage and demographic variables such as gender, district of employment, school type, professional seniority, and length of service at school. On the basis of these findings, it is concluded that from childhood onwards, experiencing failure is not a threat, but a normal outcome and a way to improve oneself. Based on these findings, it is thought that perceiving failure as a normal outcome and an opportunity for self-improvement rather than a threat, and developing a positive and accepting perspective towards the self from childhood can reduce the need to resort to self-sabotage tendencies.